1985
DOI: 10.7326/0003-4819-103-4-579
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies Against Thyroid Hormones or lodothyronine

Abstract: The presence of antithyroid hormone autoantibodies in the sera of patients with thyroid and nonthyroid disorders is a well-known condition. When circulating thyroid hormones bind to the patients' immunoglobulins, serum levels of total and free thyroid hormones are often in discordance with clinical features. This problem occurs because the autoantibodies can interfere with radioimmunoassays. To avoid inappropriate treatment of such patients, it is clinically important to consider the presence of autoantibodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
38
0
6

Year Published

1986
1986
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(47 citation statements)
references
References 67 publications
3
38
0
6
Order By: Relevance
“…These observations suggest that the patient had biologically inactive glucagon of nontumorous origin or had some interference factor with the present radioimmunoassay (RIA) system in plasma. Gel filtration studies showed that the glucagon immunoreactivity was mainly eluted in the v-globulin fraction and this is in agreement with the finding that the glucagon level in the supernatant after removing the y -globulin fraction by PEG was Autoantibodies to insulin [8], thyroid hormone [9], PRL [10] and glucagon [11] have been reported.…”
Section: Discussionsupporting
confidence: 75%
“…These observations suggest that the patient had biologically inactive glucagon of nontumorous origin or had some interference factor with the present radioimmunoassay (RIA) system in plasma. Gel filtration studies showed that the glucagon immunoreactivity was mainly eluted in the v-globulin fraction and this is in agreement with the finding that the glucagon level in the supernatant after removing the y -globulin fraction by PEG was Autoantibodies to insulin [8], thyroid hormone [9], PRL [10] and glucagon [11] have been reported.…”
Section: Discussionsupporting
confidence: 75%
“…A prevalência dos THAAb na população é de 0 a 1,8% e cerca de 1 a 10% nas doenças autoimunes tireoidianas e não tireoidianas (117,119). A prevalência varia de acordo com o método utilizado e o grupo de pacientes analisados (120,121). Os THAAb se ligam ao T 4 e T 3 marcado e ao T 4 e T 3 da amostra levando a resultados falsamente elevados ou diminuídos de T 4 e T 3 livre e/ou total dependendo do método utilizado (118,122).…”
Section: Fatores Interferentes Nos Ensaios De T 4 E T 3 Total E Livreunclassified
“…Immunoglobulins have also been found to interfere in immunoasays, particularly in patients with thyroid autoimmune disease (3,7). Most often such a condition results in mild to moderate elevation in the levels of the thyroid hormones due to increased binding capacity of plasma proteins (5).…”
Section: Indian Journal Of Clinical Biochemistry 1997 12 (I) 40-44mentioning
confidence: 99%
“…It is very rare that such autoantibodies are generated against the thyroid hormones themselves (2,3). The presence of these antibodies in serum does not onty complicate the clinical manifestations of the disease but also interferes with the estimation of total and free hormones by immuno assay (3,4,5).…”
mentioning
confidence: 99%
See 1 more Smart Citation